Faktor Yang Berhubungan dengan Kejadian Diare pada Balita di Wilayah Kerja Puskesmas Suro Kecamatan Suro Kabupaten Aceh Singkil Tahun 2022 - Hambali Manik; Vera Nazhira Arifin; Radhiah Zakaria (Yayasan Literasi Sains Indonesia, 2022)
Diarrhea is a condition in which a person defecates with a smooth or watery consistency, and is repeated several times each day. Diarrhea is one of the main causes of morbidity and mortality in infants and children. This study aims to determine the factors associated with the incidence of diarrhea in children under five in the working area of ​​the Suro Health Center, Suro District, Aceh Singkil Regency. This research is analytic with cross sectional design. Collection by interview using questionnaires and medical record observations. The population in this study were 201 toddlers. The sample in this study was 66 toddlers using random sampling technique. This research was conducted on January 5-20 2022. The statistical test used was the chi-squere test with the help of SPSS. The results of the univariate study showed that children suffered from diarrhea 68.18%, mother's knowledge was not good (54.5%), negative attitude (40.9%) and not PHBS (47%). The results of the bivariate analysis showed that there was no relationship between knowledge (p value = 0.11) with the incidence of diarrhea and there was a relationship between attitudes (p value = 0.008), PHBS (p value = 0.003) with the incidence of diarrhea. The conclusion of this study is that knowledge, attitudes and PHBS are one of the risk factors associated with the incidence of diarrhea in children under five at the Suro Health Center, Suro District, Aceh Singkil Regency in 2022. It is recommended that the Public Health Center conduct health education about diarrhea and clean and healthy living behavior (PHBS). especially in terms of preventing diarrhea to be more intensive with various approaches that are more attractive to the public.